A power-aware master and bridge scheduling scheme for bluetooth scatternets. (7th December 2006) - Sural, Shamik; Kumar, Mukesh; Sharma, Navin K.; Roy, Rajarshi
We propose an intra-piconet and inter-piconet scheduling scheme for Bluetooth in which a master assigns priority to each slave based on its packet arrival rate, available buffer space and the number of messages stored in the master buffer for that slave. The number of times a particular slave is polled by its master in succession is dependent on the assigned priority. The slaves know the polling sequence in advance and go to a power-saving mode during the intervening time interval. For bridge scheduling, a bridge is assigned to each piconet for a quantum of time that is determined by the inter-piconet traffic. We compare performance of the proposed scheme with other existing methods by simulation studies.